2018
DOI: 10.1097/sap.0000000000001169
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Peritendinous Adhesion Formation After the Flexor Tendon Surgery in Rabbits

Abstract: Local application of 5-FU significantly reduced peritendinous adhesion. Local IFN-α and IFN-β had no significant effect on the prevention of peritendinous adhesion formation. The strength of the repair was not affected by these cytokines and 5-FU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Tendon adhesion mostly occurs after tendon surgery and joint immobilization. Several mechanisms have been implicated in the modulation of adhesion formation, including the regulation of the TGF-β signaling pathway, oxidative stress, and the inflammatory response [ 3 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tendon adhesion mostly occurs after tendon surgery and joint immobilization. Several mechanisms have been implicated in the modulation of adhesion formation, including the regulation of the TGF-β signaling pathway, oxidative stress, and the inflammatory response [ 3 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two pathways are considered to participate in tendon repair. The intrinsic repair pathway involves the internal repair function of tenocytes, the extrinsic repair process involves the invasion of cells from the outside of tendon and finally promotes the formation of adhesion [ 3 , 4 ]. As the pathophysiological mechanism of tendon adhesion is not clear, the prevention and treatment of tendon adhesion is still facing challenges.…”
Section: Introductionmentioning
confidence: 99%
“…In an experimental study using local interferon-α, interferon-β and 5-fluorouracil, 5-fluorouracil was shown to prevent adhesion with anti-inflammatory effect. [ 28 ] In another study, local vitamin E analogue was shown to reduce postoperative adhesion by antioxidant and antifibrotic effects in an experimental chicken model with flexor digitorum profundus tendon injury. [ 12 ] Reduced postoperative adhesion was shown in another study where collagen-elastin matrix was used to prevent postoperative adhesion in an experimental rabbit model undergoing flexor tendon repair.…”
Section: Discussionmentioning
confidence: 99%
“…Effective inhibition of the formation of peritendinous adhesions is related to the blocking of crucial cellular targets and associated downstream signals in the adhesion formation pathway . However, the mechanisms involved in peritendinous adhesion, especially crucial cellular targets, have not been clarified.…”
Section: Discussionmentioning
confidence: 99%